2015
DOI: 10.1016/j.cancergen.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mevalonate pathway affects epigenetic regulation in cancer cells

Abstract: The mevalonate pathway provides metabolites for post-translational modifications such as farnesylation, which are critical for the activity of RAS downstream signaling. Subsequently occurring regulatory processes can induce an aberrant stimulation of DNA methyltransferase (DNMT1) as well as changes in histone deacetylases (HDACs) and microRNAs in many cancer cell lines. Inhibitors of the mevalonate pathway are increasingly recognized as anticancer drugs. Extensive evidence indicates an intense cross-talk betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 122 publications
(153 reference statements)
4
88
0
1
Order By: Relevance
“…VEGF and hypoxia inducible factor-α suppression [135] as well as inactivation of epidermal growth factor receptors [136]. There is also a report showing that bisphosphonates target the three most epigenetic cell levels, namely DNA methylation, histone deacetylation and microRNAs [137].…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…VEGF and hypoxia inducible factor-α suppression [135] as well as inactivation of epidermal growth factor receptors [136]. There is also a report showing that bisphosphonates target the three most epigenetic cell levels, namely DNA methylation, histone deacetylation and microRNAs [137].…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…We further investigated, which mechanisms are responsible for the increase of IL‐33. It was shown previously that the MVA pathway inhibitors simvastatin and ibandronate affect epigenetic regulation in cancer cells . We demonstrate here that the promoter region of IL‐33 comprises a more open chromatin structure in fluvastatin‐treated cardiac cells compared to untreated cells as analysed by promoter accessibility.…”
Section: Discussionmentioning
confidence: 50%
“…It was shown previously that the MVA pathway inhibitors simvastatin and ibandronate affect epigenetic regulation in cancer cells. 35 We demonstrate here that the promoter to a variety of proteins as post-translational modifications known as protein prenylation (protein farnesylation and geranylgeranylation). 56 We showed that GGPP abolished IL-33 expression induced by both statins and BPs, whereas only the effect of statins on IL-33 expression was reduced by MVA supplementation.…”
Section: Discussionmentioning
confidence: 76%
“…The first study showed that the treatment of breast cancer, prostate cancer and osteosarcoma cells with physiologically relevant concentrations of simvastatin induced down-regulation on DNMT1 expression at the mRNA and protein levels [62]. The second one showed that the lovastatin treatment of colorectal cancer cells reduced the DNMTs level and BMP gene expression as a result of the gene promoter demethylation [63].…”
Section: The Role Of H 2 S In the Cholesterol-dependent Regulation Ofmentioning
confidence: 99%
“…Consequently, not a surprise that cholesterol metabolism affects epigenetics, particularly DNA methylation pattern. It turned out that several studies had proved the effect of mevalonate pathway inhibitors -statins -on DNMTs expression; however, they provide no evidence of a direct role of the Ras-ERK signaling [62][63][64].…”
Section: The Role Of H 2 S In the Cholesterol-dependent Regulation Ofmentioning
confidence: 99%